How the short run effects of Brexit on trade, investment and GDP have been miscalculated in some recent work - Patrick Minford; Zheyi Zhu (Cardiff University, Cardiff Business School, 2023)
We look for statistically significant effects of Brexit events in UK data relationships. We find evidence of trade disruption by Brexit departure from the single EU market, much as we would expect. However, with investment, we find no statistically significant effects of Brexit. With GDP, inflation and interest rates we find some positive effects due to the fall in the pound. Previous work using weighted averages of selected other countries to mimic UK behaviour is inconsistent with economic theory stressing the key role of idiosyncratic country structure and shocks; it is also vulnerable to selection bias and does not test for the statistical significance of Brexit events, which have occurred in the context of enormous turbulence in the past few years in all economies due to Covid and the Ukraine war, besides accompanying large fiscal and monetary policy fluctuations.
Keywords: 330